2020
DOI: 10.3390/microorganisms8121885
|View full text |Cite
|
Sign up to set email alerts
|

Anti–SARS-CoV-2 Antibody Responses in Convalescent Plasma Donors Are Increased in Hospitalized Patients; Subanalyses of a Phase 2 Clinical Study

Abstract: We evaluated the antibody responses in 259 potential convalescent plasma donors for Covid-19 patients. Different assays were used: a commercial ELISA detecting antibodies against the recombinant spike protein (S1); a multiplex assay detecting total and specific antibody isotypes against three SARS-CoV-2 antigens (S1, basic nucleocapsid (N) protein and receptor-binding domain (RBD)); and an in-house ELISA detecting antibodies to complete spike, RBD and N in 60 of these donors. Neutralizing antibodies (NAb) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
73
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 42 publications
(89 citation statements)
references
References 36 publications
14
73
1
1
Order By: Relevance
“…The optimal rule utilized the best performing readout (RBD antigen) whose specificity was further enhanced by requiring consensus (AND) with either S1, N, or both readouts (Table 3 ). By using the readout against the RBD antigen as basis, the RBD & N|S1 rule has the added benefit of potentially informing on the presence of neutralizing antibodies as well 11 , 20 . Additionally, by utilizing the readout against N, the rule can decrease the effects of potential antibody cross-reactivity that exists against the S proteins that are conserved between coronaviruses.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal rule utilized the best performing readout (RBD antigen) whose specificity was further enhanced by requiring consensus (AND) with either S1, N, or both readouts (Table 3 ). By using the readout against the RBD antigen as basis, the RBD & N|S1 rule has the added benefit of potentially informing on the presence of neutralizing antibodies as well 11 , 20 . Additionally, by utilizing the readout against N, the rule can decrease the effects of potential antibody cross-reactivity that exists against the S proteins that are conserved between coronaviruses.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is one of the few studies showing that the levels of the adaptive humoral immune response to SARS-CoV-2 expressed as plasma concentrations of antibodies do not correlate with the presence of symptomatic disease. In contrast, others have suggested that factors such as high viral load, disease severity, and older age likely correlate with increased responsiveness of humoral immunity; however, these studies included hospitalized COVID-19 patients [11,[23][24][25]. Interestingly, in their most recent study, Sasisekharan et al [26] showed that anti-S1 and anti-RBD antibody levels could differentiate mild from moderate and severe cases, whereas anti-N antibodies could not clearly distinguish these categories, suggesting that associations between antibody titers and COVID-19 severity likely depend on the SARS-CoV-2-specific immunoassay used.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports so far have analyzed immune responses to SARS-CoV-2 infection during the course of COVID-19 and after a relatively short follow up [25][26][27]; however, data on the long-term effects of the infection on immune responses are sparse [11]. To identify immune variables associated with SARS-CoV-2 infection that may persist following COVID-19 resolution, we evaluated in detail the immune profile of a cohort of CP donors assessed at median 60 days after either the onset of symptoms or a positive PCR result.…”
Section: Discussionmentioning
confidence: 99%